Cell-free circulating DNA integrity is an independent predictor of impending breast cancer recurrence - Cheng, Jie; Cuk, Katarina; Heil, Jörg; Golatta, Michael; Schott, Sarah; Sohn, Christof; Schneeweiss, Andreas; Burwinkel, Barbara; Surowy, Harald (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.17384 Jie Cheng, Katarina Cuk, Jörg Heil, Michael Golatta, Sarah Schott, Christof Sohn, Andreas Schneeweiss, Barbara Burwinkel, Harald Surowy